Analisis Kritis Akuntabilitas Pengelolaan Dana Desa Berdasarkan Teori Konflik Karl Marx - Putri, Dina Amalya; Sakti, Dwi Putra Buana; Sokarina, Ayudia (E-Jurnal Akuntansi, 2022)
This study aims to critically analyze the accountability of village fund management in X Village based on Karl Marx's Conflict Theory. The method used is qualitative research with a single-case case study approach. Data analysis was carried out using Karl Marx's Conflict Theory. A total of 5 informants. The results of the study revealed that the implementation of village funds did not involve the community, there was dominance of the village head in decision making, budget markups, fictitious accountability reports, there was no openness of the village head and the submission of accountability reports was not timely. Theoretically, the results of this study justify the occurrence of conflict theory as a perspective in the context of managing village funds. The conflict here emphasizes the pluralistic nature of society and the imbalance in the distribution of power that occurs between various groups, because of the power possessed, the elite group also has the power to create regulations. Thus, it is necessary to establish a praxis in the form of transparent and process-oriented village fund management by involving the active participation of the community . Keywords: Accountability; Village Funds; Conflict Theory; Karl Marx.